LEARNING AS PRECONDITION TO STAY ACTIVE IN LABOUR MARKET FOR ELDER PEOPLE - Rutkiene, Ausra; Lengvinienе, Silva (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2016)
Nowadays society is getting older in European countries. Technologies, speed of life requires higher level of abilities and competencies. People who are 55 and older are very experienced in their workplace but some of them cannot catch changes in their professional area. Quantitative research results demonstrate that learning is one of important factors which helps to stay active in labor market for longer time. People participate in different learning activities to get more professional competencies or to change qualification, to get higher salary or learning was required from employer. The main barriers for learning were mentioned: lack of time, no needed learning at all and lack of information. People who have longer tradition and personal motivation use different learning ways more often, and they say that learning as precondition to stay active in labor market for elder people.